Expression of costimulatory molecules in the bovine corpus luteum - Pate Joy L; Davis John S; Cannon Matthew J (BMC, 2007)
Abstract Background Bovine luteal parenchymal cells express class II major histocompatibility complex (MHC) molecules and stimulate class II MHC-dependent activation of T cells in vitro. The ability of a class II MHC-expressing cell type to elicit a response from T cells in vivo is also dependent on expression of costimulatory molecules by the antigen presenting cell and delivery of a costimulatory signal to the T cell. Whether bovine luteal parenchymal cells express costimulatory molecules and can deliver the costimulatory signal is currently unknown. Methods Bovine luteal tissue was collected during the early (day 5; day of estrus = day 0), mid (day 11-12), or late (day 18) luteal phase of the estrous cycle, and at 0, 0.5, 1, 4, 12 or 24 hours following administration of PGF2alpha to cows on day 10 of the estrous cycle. Northern analysis was used to measure CD80 or CD86 mRNA concentrations in luteal tissue samples. Mixed luteal parenchymal cell cultures and purified luteal endothelial cell cultures were prepared, and real-time RT-PCR was used to examine the presence of CD80 and CD86 mRNA in each culture type. Monoclonal antibodies to CD80 and CD86 were added to a mixed luteal parenchymal cell-T cell co-culture in vitro T cell proliferation assay to assess the functional significance of costimulatory molecules on activation of T lymphocytes by luteal parenchymal cells. Results Northern analysis revealed CD80 and CD86 mRNAs in luteal tissue, with greatest steady-state concentrations at midcycle. CD80 and CD86 mRNAs were detected in mixed luteal parenchymal cell cultures, but only slight amounts of CD80 (and not CD86) mRNA were detected in cultures of luteal endothelial cells. Luteinizing hormone, PGF2alpha and TNF-alpha were without effect on concentrations of CD80 or CD86 mRNA in mixed luteal parenchymal cells cultures. Anti-CD80 or anti-CD86 monoclonal antibodies inhibited T cell proliferation in the in vitro T cell proliferation assay. Conclusion It can be concluded from this study that parenchymal cells within the bovine CL express functional costimulatory molecules that facilitate interactions between with T cells, and these components of the antigen presentation pathway are expressed maximally in the midcycle CL.